Study of Power Flow and Harmonics when Integrating Photovoltaic into Microgrid - Robi Kurniawan; Muhammad Daud; Arnawan Hasibuan (Indonesian Mechanical Electrical and Industrial Research Society (IMEIRS), 2023)
Power system stability issues and the lack of studies of the impact of relevant renewable energy networks are factors hindering the use of large-scale integration of renewable energy sources. This study focuses on examining the impact of photovoltaic system integration on the power stability of the power grid. The integration of this photovoltaic involves the analysis of the static and dynamic state of the electrical network. Load flow simulation is performed to assess the performance of static conditions of the power grid. Furthermore, dynamic analysis is carried out by applying 3-phase short circuits at critical points of the network and observing how harmonic and stability in the system. The simulation was carried out using the ETAP 19.0. Simulations of existing conditions and after penetration of the photovoltaic system showed the buses had THDv and THDI values below the permissible standards, respectively. In addition, the existing power flow simulation experiences a voltage drop from the nominal voltage. Masalah stabilitas sistem tenaga dan kurangnya studi akan dampak dari jaringan energi terbarukan yang relevan merupakan faktor yang menghambat penggunaan integrasi skala besar dari sumber energi terbarukan. Penelitian ini fokus mengkaji dampak integrasi sistem fotovoltaik pada stabilitas daya jaringan listrik. Integrasi sistem fotovoltaik ini melibatkan analisis keadaan statis dan dinamis dari jaringan listrik. Simulasi aliran beban dilakukan untuk menilai kinerja kondisi statis dari jaringan listrik. Selanjutnya, analisis dinamik dilakukan dengan menerapkan hubung singkat 3 fasa pada titik-titik kritis jaringan dan mengamati bagaimana harmonisa dan stabilitas pada sistem. Simulasi dilakukan dengan menggunakan perangkat lunak ETAP 19.0. Simulasi kondisi sebelum dan setelah penetrasi sistem fotovoltaik menunjukkan bus masing-masing memiliki nilai THDv dan THDI dibawah standar yang diperbolehkan. Selain itu, simulasi aliran daya kondisi sebelum integrasi mengalami jatuh tegangan dari tegangan nominal.